The Spectrum of Pedagogical Orientations of Malawian and South African Physical Science Teachers towards Inquiry. Issue 2 (3rd May 2016) - Ramnarain, Umesh; Nampota, Dorothy; Schuster, David
Abstract : This study investigated and compared the pedagogical orientations of physical sciences teachers in Malawi and South Africa towards inquiry or direct methods of science teaching. Pedagogical orientation has been theorized as a component of pedagogical content knowledge. Orientations were characterized along a spectrum of two variants of inquiry and two variants of direct instruction. Teacher preferences for pedagogy were measured using case-based assessment items which depicted actual scenarios for teaching particular physical sciences topics and provided four alternative teaching method options. Item topics were common to both the Malawian and South African science syllabuses. Response data were obtained from 164 Malawian high school physical sciences teachers at community, conventional and grant-aided schools, for comparison with previous South African data. Analyses produced pedagogical orientation profiles for each teacher and item in terms of the distribution of choices between the four options and these were aggregated by school type and compared with the corresponding profiles for South African teachers on the same items. Responses to items covered the whole spectrum of approaches, although relative proportions depended on teacher, topic, type of school and country. Aggregated responses for both countries tended more toward variants of inquiry than of direct instruction. In some cases, Malawian teachers had an unexpectedly strong direct didactic preference. A direct didactic orientation was mainly prevalent amongst teachers from disadvantaged Malawian community schools and South African rural schools. South African teachers from suburban schools exhibited a stronger guided inquiry orientation than their Malawian counterparts from grant-aided schools. In contrast, teachers at Malawian conventional schools had a stronger preference to adopt variants of inquiry (guided and open) than South African teachers at corresponding township schools. Teachers at more privileged schools, that is, Malawian grant-aided and South African suburban schools, showed stronger guided- and open-inquiry orientations than teachers at less privileged schools. School type and contextual circumstances affected teachers' pedagogy choices in both countries, having a substantial influence on the approaches that teachers would adopt in their own situations.